2003
DOI: 10.1055/s-2003-37969
|View full text |Cite
|
Sign up to set email alerts
|

Schwannoma of the Lateral Ventricle: Eight-Year Follow-Up and Literature Review

Abstract: Intracerebral and intramedullary schwannomas are uncommon; but, in general, spinal intramedullary schwannomas are more frequent than intracerebral schwanomas. We present a case of right lateral ventricle schwannoma in a 21-year-old man and review the associated literature. The 21-year-old right-handed man presented with loss of the left-eye vision approximately 8 months before referral to an ophthalmologist. The patient was immediately subjected to computed tomography (CT) scan, which showed an enhanced lesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
20
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 13 publications
(30 reference statements)
3
20
1
1
Order By: Relevance
“…12,26,36 On gross pathological examination, intracerebral schwannomas have been described as gray, firm, rubbery, mildly to moderately vascular, occasionally gritty, not infrequently cystic, and with well-defined planes of cleavage. 17,26,31,50 These characteristics were also seen in our case series, although in Case 2 it was the capsule of the tumor, much more than its interior, that demonstrated hypervascularity.…”
Section: Discussionsupporting
confidence: 77%
“…12,26,36 On gross pathological examination, intracerebral schwannomas have been described as gray, firm, rubbery, mildly to moderately vascular, occasionally gritty, not infrequently cystic, and with well-defined planes of cleavage. 17,26,31,50 These characteristics were also seen in our case series, although in Case 2 it was the capsule of the tumor, much more than its interior, that demonstrated hypervascularity.…”
Section: Discussionsupporting
confidence: 77%
“…It has also been suggested that intra-axial schwannomas could arise from neural crest cells displaced into the nervous system as a result of failed migration in embryonic life 1 . This disordered embryogenesis theory may account for the relationship between intraventricular schwannomas and other neurocutaneous syndromes such as neurofibromatosis, Hirschprung's disease, and Waardenburg's syndrome 3,6 .…”
Section: Discussionmentioning
confidence: 99%
“…Schwannomas account for approximately 8% of all intracranial neoplasms 6 . Most originate from the vestibular portion of the cranial nerve (CN) VIII.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations